Pathways for Change: 10 Theories to Inform Advocacy and Policy Change Efforts - Stachowiak, Sarah (Center for Evaluation Innovation, 2013)
One of our most popular publications, this brief, produced in collabor ation with ORS Impact, summarizes 10 theories grounded in social scien ce about how policy change happens. The theories can help to untangle beliefs and assumptions about the inner workings of the policymaking p rocess and identify causal connections supported by research to explai n how and why a change may or may not occur. Advocates of all stripes seek changes in policy as a way to achieve impact at a scale and degre e of sustainability that differs from what can be achieved through dir ect services or programs alone. Advocates and funders each come to pol icy work with a set of beliefs and assumptions about how change will h appen, and these beliefs shape their thinking about what conditions ar e necessary for success, which tactics to undertake in which situation s, and what changes need to be achieved along the way. These worldview s are theories of change, whether or not they explicitly have been sta ted or documented as such. When articulated as theories of change, the se strategy and belief system roadmaps can clarify expectations intern ally and externally, and can facilitate more effective planning and ev aluation. This brief lays out 10 theories grounded in diverse social s cience disciplines and worldviews that have relevance to the world of advocacy and policy change. Global and tactical theories include: - “L arge Leaps” or Punctuated Equilibrium theory - “Policy Windows” or Age nda-Setting theory - “Coalition” theory or Advocacy Coalition Framewor k - “Power Politics” or Power Elites theory - “Regime” theory - “Messa ging and Frameworks” theory - “Media Influence” or Agenda-Setting theo ry - “Grassroots” or Community Organizing theory - “Group Formation” o r Self-Categorization theory - “Diffusion” theory or Diffusion of Inno vations The theories can help to untangle beliefs and assumptions abou t the inner workings of the policymaking process and identify causal c onnections supported by research to explain how and why a change may o r may not occur. This piece is not meant to be comprehensive of all po ssible relevant theories and approaches; rather, it introduces and ill ustrates a handful of theories that may be useful to advocates, funder s, and evaluators.